PERBANDINGAN HITUNG LEUKOSIT METODE HEMATOLOGIANALYZER DAN HEMOSITOMETER DI RSUD TOTO KABILA BONEBOLANGO - Junelan Ningsih A.S Pandju Pandju; Rita Amini Warastuti; Srikit Nurkamiden (Journal of Health, Technology and Science (JHTS), 2023)
Examination of leukocyte count is a routine blood test that is widely requested in health care units, both clinics, health centers or even in hospitals. This study aims to establish the diagnosis of the disease. One laboratory examination, namely a hematological examination, to find out the comparison of leukocyte counts with the Hematology Analyzer and Hemocytometer methods at Toto Kabila Hospital, Bone Bolango Regency. The type of research used is Observational Analytic Research with a quantitative approach, analytical research is research that looks for relationships between variables, namely by analyzing comparisons. The sample size taken was 30 samples with the sampling technique using purposive sampling. This type of research wanted to see the results of a comparison of leukocyte counts using the hematology analyzer and hemocytometer methods at Toto Kabila Hospital, Bone Bolango Regency. The results obtained during this research areThe results of a comparison of leukocyte examination using a hematology analyzer and hemocytometer were obtained0.039 <0.05, where the null hypothesis (H0) means rejected and the alternative hypothesis (Ha) means accepted, so it can be concluded that the data obtained is different.